Understanding the Relationship between SelfConstruals, Self-Esteem, Social Support, and the Sociocultural Adaptation of African Students in Northern Cyprus - Tchoh, Bennett K.; Mertan, E. Biran (Journal of International Students, 2018)
In this study, we explored the relationship between self-construals, selfesteem, social support, and the sociocultural adaptation of African students in Northern Cyprus. Based on the responses received from 112 students from Sub-Saharan Africa studying in Northern Cyprus, the results indicated that only the interdependent self-construal and social support predicted sociocultural adaptation. This study highlights the importance of social support and relatedness for international students from Sub-Saharan Africa studying in Northern Cyprus.